Layanan Pengaduan Jalan dan Jembatan Dalam Aplikasi SIMANJA (Sistem Informasi Manajemen Jalan dan Jembatan) Dinas Pekerjaan Umum Kota Tangerang Selatan (Studi Penggunaan Layanan Berbasis Sistem Informasi Manajemen Dalam Aplikasi SIMANJA Dinas Pekerjaan Umum Kota Tangerang Selatan) - Herman, Herman; Fatahillah, Muhammad; Munawan, Rijwan; Ruhana, Faria (Jurnal Ilmiah Global Education, 2024)
The implementation and arrangement of management information systems in government and public service environments can be realized by optimizing the use of information technology which is increasingly developing with current changes. The use of information technology in an organization is a complete and interconnected unit in its work process as a system. The implementation of services based on management information systems or IT has become the standard in implementing IT-based government (E-Gov). SIMANJA is an Android-based application belonging to the South Tangerang City Public Works (PU) Department which functions as a public complaint service. However, in the application of the service, there is still a lot that needs to be improved, and there are still many people in South Tangerang who are still unfamiliar with the application. This research method uses a qualitative descriptive approach. In obtaining data, researchers used in-depth interview techniques. The results of the research are in six theoretical points where overall the South Tangerang City Public Works Department has implemented the six elements of excellent service in the SIMANJA application, although there is still room for improvement, especially in disseminating the application to the public and fast response.